On the interplay between pressure and gravitational forces in coalescing filters. (May 2022) - Starnoni, M.; Manes, C.
Abstract: This paper provides insights into processes governing oil–mist filtration in coalescing filters. In particular, it resolves an apparent inconsistency between different published studies regarding the occurrence (or not) of internal gravity-induced flows. As a result of this, it also clarifies whether in industrially-relevant scenarios such as those pertaining to vertical filter cartridges, non-homogeneous vertical saturation patterns are triggered by these internal flows or are just a result of different oil loading rates. To address these issues, we use Eulerian–Lagrangian CFD simulations, which properly account for the effects of turbulent diffusion of liquid aerosol particles, to replicate an experimental setup available in the literature. In order to interpret results data, we introduce a new dimensionless number, termed S M, defined as the ratio between pressure gradient and gravitational forces, which provides a bulk characterization of the flow and allows to assess whether internal gravity-induced flows, in a given cartridge–oil system, should be expected or not. We show that S M explains well the few experimental data available in the literature and identifies specific behaviors associated with limiting S M values being either very large or close to 1. Highlights: We determine why internal gravity flows are reported or not in coalescing filters. We properly account for turbulent diffusion of liquid aerosol particles. A new dimensionless number S M characterizes bulk flow inside a coalescing filter. For S M >>1, flow is essentially 1D and there is no internal gravity-induced flow. For S M ≈ 1, there is internal gravity-induced flow.